Systematic Literature Review: The Effect of Breastfeeding on the Incidence of Stunting in Infants and Children - Sibarani, Benly Levi Andreas; Utami, Putri (Asian Journal of Healthcare Analytics, 2024)
Child malnutrition affects children's health in terms of morbidity and mortality rates. Stunting remains a persistent nutritional issue among children that has yet to be effectively addressed. This study aims to examine the impact of breastfeeding on the incidence of stunting in infants and young children. This study reviewed literature from two databases, PubMed and Google Scholar, based on predetermined criteria. The methodology was conducted using a systematic approach from the literature. The results of the study obtained nine articles that met the criteria, then continued with a systematic review. Three studies showed the role of breastfeeding as a significant protective factor. Five studies identified a link between breastfeeding and stunting incidence, while another study found no such association. The presence of a significant relationship and the protective role of breastfeeding against stunting are crucial in efforts to lower the risk of stunting among toddlers and young children.